Meningkatkan Kompetensi Kewirausahaan Mahasiswa UNIMEN melalui Kunjungan Industri Rumah Produksi Bachis Pinrang - Azhari, Burnama; Zarina, Zarina; Haerusman, Haerusman; Nuha, Uli; Widiawati, Wilda; Potton, Zainal (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2025)
This community service program aimed to enhance the entrepreneurial competence of students at the University of Muhammadiyah Enrekang (UNIMEN) through a practical learning experience. The program focused on addressing the low interest in entrepreneurship among Indonesian students by providing real-world into business operations. A participatory active method was employed, involving 91 students from three study programs. The program included: 1) students were involved in setting objectives and preparing materials for the visit, 2) an industrial visit to Bachis Pinrang, a successful home-based banana chips produvtion house, where students observed the production process, interviewed the owner, and engaged in discussions, 3) gathering feedback from students to assess the program’s effectiveness. The industrial visit provided students with valuable practical experience and a deeper understanding of business management. It also exposed them to a successful entrepreneurial model, inspiring them to consider entrepreneurship as a career path. Preliminary findings indicate an increase in student’s motivation and practical skills related to entrepreneurship. Further evaluation will be conducted to measure the program’s impact on student’s entrepreneurial knowledge, attitudes, and skills.